2014
DOI: 10.1371/journal.pone.0098461
|View full text |Cite
|
Sign up to set email alerts
|

Human CD4+ T Cell Responses to the Dog Major Allergen Can f 1 and Its Human Homologue Tear Lipocalin Resemble Each Other

Abstract: Lipocalin allergens form a notable group of proteins, as they contain most of the significant respiratory allergens from mammals. The basis for the allergenic capacity of allergens in the lipocalin family, that is, the development of T-helper type 2 immunity against them, is still unresolved. As immunogenicity has been proposed to be a decisive feature of allergens, the purpose of this work was to examine human CD4+ T cell responses to the major dog allergen Can f 1 and to compare them with those to its human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…These homologous lipocalins showed similar results like Lcn-1 and Can f 1 regarding the induction of IL-12 and T-helper cell subtypes ( Fig. 5) and Liukko et al [38] show that lipocalin derived peptides alone are not able to drive differential immune responses which supports our view that the interaction of lipocalins with DCs is essential to define the type of immune response. More studies might be necessary to clear these discrepancies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These homologous lipocalins showed similar results like Lcn-1 and Can f 1 regarding the induction of IL-12 and T-helper cell subtypes ( Fig. 5) and Liukko et al [38] show that lipocalin derived peptides alone are not able to drive differential immune responses which supports our view that the interaction of lipocalins with DCs is essential to define the type of immune response. More studies might be necessary to clear these discrepancies.…”
Section: Discussionsupporting
confidence: 87%
“…Although most of the data shown in these reports are not directly comparable to our study, some are still contradictory. Virtanen and colleagues found that mammalian lipocalin allergens do not exhibit DC-activating capacity and found no differences in the CD4 + T cell responses to the two homologous lipocalins 38,39 while Preston et al . 40 found immunomodulatory activity of hard tick-derived lipocalins and Roth-Walter et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that human CD4+ T cell responses are similar to both the major dog allergen Can f 1 and its human homologue tear lipocalin [7]. Bites from rodents can also cause anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…T‐cell responses have been found to be ‘suboptimal’ for Can f 1 , although resembling those to human LCN1 . Can f 4 T‐cell responses were shown to be a Th2‐deviated memory response, in part to peptides with promiscuous HLA‐binding capacity , whereas the DR4–DQ8 haplotype and T‐cell receptor Vbeta T‐cell subset were indicative for the absence of Can f 1 allergy .…”
Section: Comparing Structural Features Of Lipocalinsmentioning
confidence: 99%